Modifikasi Oven Biasa Menjadi Oven Vakuml - Subandi subandi (Jurusan Teknologi Pertanian, 2020)
The limited quantity and types of facilities for practicum, independent business projects and research, both lecturer and student research, is a problem that often arises and requires solutions to overcome it, one way to overcome the problem of limitations in types of practicum facilities is to modify existing equipment so that it can be done. used for other functions in accordance with the demands of the development of student and lecturer research studies. Modification of an ordinary oven into a vacuum oven is a set of drying ovens that are coupled with a suction pump and equipped with a vacuum gauge to measure the level of vacuum. A vacuum oven is a drying device with a low temperature, with the working principle in a vacuum that the boiling point of moisture is lower than the boiling point in atmospheric conditions so as to speed up the drying time and reduce the amount of damaged nutrients in the dried material due to drying. This drying method is suitable for materials that have high temperature sensitivity or are volatile due to their short drying time, one of which is food ingredients. At high temperature drying, the vitamin content in food is easily degraded and damaged. The modified vacuum oven can be used to dry materials from the types of leaves, fruit and tubers that were thinned using a temperature of 60°C, a vacuum level of -0.5 atm for 2 hours.